Selected Papers from 1st International Electronic Conference on Biological Diversity, Ecology, and Evolution (BDEE 2021) - Wink, Michael (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Due to the COVID-19 pandemic, the character of academic conferences has changed. Formerly, conferences required the physical presence of their members and audiences. However, travel restrictions due to the pandemic caused a shift in the traditional conference format, thus resulting in the rise of online conferences after 2020. In 2021 and 2022, the journal "Diversity" similarly organized online conferences. The well-attended online conference in March of 2021 attracted a wide range of speakers on biodiversity, ecology and evolution, as well as on 17 publications from this Special Issue. The publications cover several timely aspects of biodiversity, such as the importance of invasive species, the ecology of urbanization, the effects of drought on wildlife in Southern Africa, the results of human activities on insect, mammal, bird, reptile and amphibia populations, and the genetic diversity of animal breeds, microbiomes and planktonic organisms. Additionally, taxonomic and biosystematic topics are also covered in several SI publications.